Study on axial compression behavior of thin-walled pressurized steel pipe column - Boxuan Xu; Haishen Wang; Wu Jiang; Xianzhi Zeng; Peng Pan (Engineering Structures, 2026)

Long-term organic amendments regulate cbbL-harboring bacterial community via soil physicochemical properties and enzyme activities in a paddy soil - Jiangbing Xu; Boxuan Li; Yuhao Wu; Lei Liu; Guoyi Zhou; Xiaoli Liu; Ling Chen; Meng Wu; Xiaoyan Ma; Catherine Preece; Daming Li; Ming Liu (Journal of Soils and Sediments, 2026)

Construction of recombinant OPIV3 virus vectoring bivalent Mycoplasma ovipneumoniae adhesins - Xu Zhang; Yijia Liu; Boxuan Yin; Changyan Li; Miao sun; Qinghong Xue; Jinhai Huang (Archives of Virology, 2026)

Deep learning-based morphological analysis of human sperm - Yiran Xu; Yuqiu Chen; Boxuan Zhang; Yimo Yan; Hongen Liao; Ran Liu (Medical & Biological Engineering & Computing, 2026)

Raman spectral optimization for soot particles: A comparative analysis of fitting models and machine learning enhanced characterization in combustion systems - Longfei Chen; Yang Cao; Xuehuan Hu; Bin Zhang; Xiaoyang Chen; Boxuan Cui; Jun Xu; Tao Yu; Zheng Xu (Building and Environment, 2025)

21Ne and 10Be dating of folded fluvial terraces: Constraining active deformation of the Guman fold along the foothill of the western Kunlun mountains (Xinjiang, China) - Jianhong Xu; Jie Chen; Tao Li; Boxuan Zhang; Ning Di; Wei Pang (Journal of Structural Geology, 2024)

Impacts and influencing pathways of urbanization on carbon–water-energy-food nexus across Chinese cities - Chenggang Li; Yong Liu; Zhenci Xu; Gang Zhao; Youhui Bao; Chengcheng Cai; Yu Lu; Yufeng Mao; Alexander Boxuan Wang; Liang Wu (Environment, Development and Sustainability, 2024)
Food, water, energy and carbon (F-W-E-C), as important factors of urban development, have synergistic effects and trade-off effects with each other. Scientifically assessing the impact of urbanization on the F-W-E-C nexus is beneficial to optimize the urban development layout and achieve the sustainable urban development. Nevertheless, extant studies have not evaluated the impact and influencing pathways of urbanization on the F-W-E-C nexus. In this study, the Coupling Coordination Degree Model is used to explore the F-W-E-C nexus of 252 prefecture-level cities in China. The panel data model and mediating effect model are utilized to study the impact of urbanization on the F-W-E-C nexus and the impact pathways. This study finds that the F-W-E-C nexus across Chinese cities is weak trade-off. The urbanization promotes the synergy of F-W-E-C. The positive impact is greater in the central cities than in the eastern and western cities, and is greater in medium-sized cities than in small cities, large cities and above. The technological progress is an important pathway of urbanization impacting the F-W-E-C nexus, and assists urbanization to generate a positive influence on the F-W-E-C nexus. This research has implications for promoting a systematic, orderly, and rational coordination development of F-W-E-C and for sustainable urbanization development in China and the world.

Chemical constituents from Mytilaria laosensis Lec. leaves and branches - Xiaofang Ye; Yingxin Liang; Boxuan Liao; Chen Ni; Huaqiang Lu; Rui He; Cuixian Zhang; Hui Xu; Jinchang Yang (Biochemical Systematics and Ecology, 2023)

Novel high-performance automatic removal method of interference points for point cloud data in coal mine roadway environment - Shaoyi Xu; Boxuan Shi; Chengtao Wang; Fangfang Xing (International Journal of Remote Sensing, 2023)

Slip partitioning and crustal deformation patterns in the Tianshan orogenic belt derived from GPS measurements and their tectonic implications - Chuanyong Wu; Peizhen Zhang; Zhuqi Zhang; Wenjun Zheng; Binbin Xu; Weitao Wang; Zhongyuan Yu; Xunye Dai; Boxuan Zhang; Kezhi Zang (Earth-Science Reviews, 2023)